EP800 Outcome and treatment of ovarian cancer: a retrospective study. (1st November 2019) - Berg, T; Nøttrup, TJ; Peen, UBS; Roed, H
Abstract : Introduction/Background: Ovarian cancer has the highest mortality rate among gynecological cancer and is the tenth most frequent cancer among women. Eighty percent of patients with advanced stage decease will experience a progression either during or after treatment. Methodology: A retrospective, observational study of all women referred to adjuvant or neoadjuvant treatment for ovarian cancer between the 1st of June 2013 and 31st of May 2014 at two university hospitals in Denmark. Results: We included 142 women with diagnosed ovarian cancer. Median overall survival from diagnosis was 48.5 months (95% CI 36.6–57.9). Median survival after first, second, third, fourth and fifth progression was 19.3 (95% CI 13.9–27.3), 11.4 (7.7–18.8), 9.5 (6.3–12.7), 8.3 (7.6–11.5), 5.6 (2.9–NA) months, respectively. Median progression-free survival from diagnosis was 15.6 months (95% CI 14.3–18.4). Median progression-free survival after first, second, third, fourth and fifth progression was 9.2 (95% CI 7.7–10.6), 6.0 (3.5–7.7), 3.3 (2.6–4.6), 4.9 (3.6–8.3), 3.0 (2.4–5.7) months, respectively. The most frequently used treatment at first progression was carboplatin and liposomal doxorubicin (n=37). The most used non-platinum containing treatment at progression was liposomal doxorubicin (n=26) followed by paclitaxel (n=23). Conclusion: Ovarian cancer remains a highly aggressive decease with most patients diagnosed in advanced stages. The treatment has not changed a lot in the last 15 years and the same is evident for the overall survival. Disclosure: Mr. Tobias Berg received an unrestricted scholarship grant from the Danish Cancer Society. The remaining authors have nothing to disclose.